A New Era of Capital Structure Choices in Technology Firms: Insights on Cultural Dimensions - Süleyman Değirmen; Mert Aktaş; Ömür Saltık; Filiz Bozagaç (Journal of Economy Culture and Society)
This study investigates the correlation between corporate financial ratios and cultural dimensions across countries in order to guide technology firms in adapting to the current financial landscape characterized by limited borrowing options and higher interest rates. Using Hofstede’s subregional continental classification, it examines the relationship betweencapital structure and value among 4,237 publicly listed technology firms in 46 countries. The study analyzes financial ratios and connects them with Hofstede’s subdimensions of individualism and uncertainty avoidance culture. The findings reveal a significant relationship between cultural dimensions and financial ratios, with individualism and uncertainty avoidance being influential factors. Countries emphasizing individuality tend to have higher borrowing rates, whereas those with a strong preference for uncertainty avoidance exhibit higher gross margins and total debt-to-equity ratios. The borrowing rate variable does not directly affect the dimensions of femininity versus masculinity and uncertainty avoidance; however, it impacts the dimension of individualism versus collectivism. Overall, this study provides valuable insights to enable technology firms to make informed decisions, manage financial structures, and effectively navigate the current financial landscape.